Characterization of inhomogeneity in microstructure at the surface layers of gear steels by Magnetic Barkhausen Noise (مجلة البحوث الأكاديمية, 2022)
The effect of gradients in hardness, microstructure and composition in the surface layers on magnetic Barkhausen noise (MBN) was investigated in two widely used gear steels. In the experiment one material was through hardened in two ways: (i) A set of Ovako 667 was hardened according to the standard process of this type and, (ii) Another set was deliberately decarburized. The other material, EN36 was gas case carburized according to the standard procedure. It was found that, the inhomogeneity in the decarburized and the case-carburized materials showed up clearly in the MBN measurements. This took the form of a two-peak MBN profiles whereas, a single peak profile was seen with the homogenous martensitic microstructure specimen. It is found that the shape of the MBN profile is significantly affected when a gradient in microstructure is induced by a gradient in carbon content. This was confirmed by metallographic examination and the microhardness tests. The result concludes that the MBN as an effective non-destructive testing technique which may replace the used destructive techniques.
Keywords: magnetic Barkhausen; Noise (MBN); carburization; decarburization